Praktik Green Hotel di Sanur, Bali: Perjalanan Menuju Ekosistem Pariwisata Pesisir yang Berkelanjutan - I Gusti Ayu Melistyari Dewi; I Nyoman Sunarta; I Made Adikampana; I Wayan Suardana (Faculty of Economics and Business, University of Mataram, 2026)
This study analyzed the implementation of the green hotel concept by hotels in Sanur, Bali, and its contribution to building a sustainable coastal tourism ecosystem. While Sanur is renowned for its tranquil environment and successful community-based tourism, the application of green practices within its hotel industry remains under-explored and inconsistent. Using qualitative methods, including interviews with hotel management and direct observation, this research identified key initiatives and the challenges hotels face in adopting sustainable practices. The findings revealed that several hotels have implemented sustainable practices in five key areas: hotel environment, energy use, tourist education, amenities, and waste management. Initiatives range from utilizing green open spaces and local building materials to using refillable amenities and composting organic waste. Some hotels also engage in community-based programs, such as providing free traditional dance training for local children. Hotels faced significant obstacles, primarily a lack of awareness among staff and guests, limited funding for higher operational costs, and the absence of clear government regulations and incentives. This study concludes that a more structured and collaborative approach is needed and supported by synergy between local government, hotel associations, and the community to provide training, monitoring, and promotion.